PENGARUH FAKTOR INTERNAL DEBITUR TERHADAP KREDIT BERMASALAH PADA PT. BANK NEGARA INDONESIA (PERSERO) Tbk CABANG PALU - Ulfa, Ulfa (Katalogis, 2017)
Problems in credit repayment derived from internal and external factors of a bank. External factors such as interest rates, foreign exchange rates, and inflation cannot be controlled by the bank so that when non-performing loan occurred due to external factors, it is considered reasonable because the risk is difficult to be predictedand minimized. This study is aimed to analyze the influence of internal debtor on non performing loans at PT. Bank Negara Indonesia (Persero) Tbk Branch Palu. The variables of debtor internal defined as the 5C principle in credit analysis. Variables of non-performing loans include accident, death and divorce (for individual borrowers); credit missmaangement, lack of knowledge and experience of the company’s management, as well as fraud (for corporate debtor). Data used in this study consistsof primary and secondary data, wich attained from questionnaires, interviews and documentation. The results based on multiple linear regressions analysis non-performing loans indicate that internal influence simultaneously has significant influence on non performing loans at PT. BNI Branch Palu. Partial test shows that character capacity and capital has positive and significant influence on performing loans; collateral and condition has insignificant influence on non performing loans at PT. BNI Branch Palu.